2017
DOI: 10.1002/jts.22197
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors, Coping Appraisals, and Social Barriers Predict Mental Health Following Community Violence: A Prospective Test of Social Cognitive Theory

Abstract: This study tested social cognitive theory of posttraumatic adaptation in the context of mass violence, hypothesizing that pre-event protective factors (general self-efficacy and perceived social support) would reduce posttraumatic stress symptoms (PTSS) and depression severity through boosting post-event coping self-efficacy appraisals (mediator). We qualified hypotheses by predicting that post-event social support barriers would disrupt (moderate) the health-promoting indirect effects of pre-event protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In a previous publication, we demonstrated that a substantial number of survivors and bereaved in the current sample, even after 26 years, entertained vivid thoughts about the disaster and what could have happened, which may be at odds with the expectations of significant others 38 . Additionally, the victims may refrain from taking advantage of the social support available, sometimes because they fear that others will perceive them as weak or because they think they will overburden their friends and families 6 , 39 , 40 . In addition, family and friends may feel uncomfortable or find it difficult to relate to the victims, withdrawing from them as a result 41 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a previous publication, we demonstrated that a substantial number of survivors and bereaved in the current sample, even after 26 years, entertained vivid thoughts about the disaster and what could have happened, which may be at odds with the expectations of significant others 38 . Additionally, the victims may refrain from taking advantage of the social support available, sometimes because they fear that others will perceive them as weak or because they think they will overburden their friends and families 6 , 39 , 40 . In addition, family and friends may feel uncomfortable or find it difficult to relate to the victims, withdrawing from them as a result 41 .…”
Section: Discussionmentioning
confidence: 71%
“… 38 Additionally, the victims may refrain from taking advantage of the social support available, sometimes because they fear that others will perceive them as weak or because they think they will overburden their friends and families. 6 , 39 , 40 In addition, family and friends may feel uncomfortable or find it difficult to relate to the victims, withdrawing from them as a result. 41 This study is the first to indicate that social support deterioration may last for decades and proposes that even though social support can be considered a protective factor in the initial phase after a trauma, social support is also a long-term outcome in itself.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond engaging with fellow healthcare workers, engagement in support with non-healthcare workers may also be critical, and can be pursued based on shared meaning and stressful pandemic experiences that transcend work environments (e.g., parenting stressors; school stressors; scarcity of resources; loss of routine; increase in stress/tension at home; grief and loss). Such diversity of support options is likely to be critical across time [ 81 ], as professional identity is not the only valid or healthy source of identity, meaning, or connection. Our multitude of roles (mother, father, sister, brother, parent, child, hobbies from which we derive identity capital) each offer inroads to sharing experiences and extracting support in meaningful ways that can promote resilience and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…If the social support network is low on resources, or the individual perceives these resources to be limited, barriers to seeking support may arise, such as a reluctance to overburden friends and family due to the feeling that they have enough to cope with already or that they would not understand. Such social support barriers have been found to have strong associations with psychological distress in previous trauma samples (Smith, Felix, Benight, & Jones, 2017 ; Thoresen, Jensen, Wentzel-Larsen, & Dyb, 2014 ). A weak existing social network may be difficult to maintain and access digitally and may not be able to provide a buffering function during the pandemic.…”
Section: Discussionmentioning
confidence: 94%